Pandemic soundscapes. Etnografie collaborative e approcci multimodali al paesaggio sonoro del coronavirus Pandemic soundscapes. Collaborative ethnographies and multimodal approaches to the coronavirus soundscape - Gianfranco Spitilli (EtnoAntropologia, 2023)
During the first phase of confinement, initiatives focused on the sound dimension of the coronavirus popped up, starting with the perception of the changing soundscape. On a digital level, through web platforms and sound capture technologies, which are also widely available via smartphones, the possibility offered by an almost unlimited interconnection has multiplied the documentation, circulation and manipulation of pandemic sound elements, which have thus become an integral part of collaborative ethnographic projects and multimodal approaches to the coronavirus soundscape.